Ethical Considerations in the Application of Enzyme-Induced Calcium Carbonate Precipitation (EICP) for Soil Improvement - Guo, Xu (International Journal of Natural Resources and Environmental Studies, 2025)
This paper systematically explores the application of enzyme-induced calcium carbonate precipitation (EICP) technology in soil improvement, along with its associated ethical considerations. First, the fundamental principles of EICP are described, wherein urease catalyzes the hydrolysis of urea to produce calcium carbonate precipitates, thereby enhancing soil structure and stability. Next, the wide-ranging applications of EICP in soil reinforcement, foundation treatment, and pollution remediation are analyzed, highlighting its notable technical advantages such as environmental friendliness, low energy consumption, and operational simplicity. However, the technology also faces several challenges, including difficulties in reaction control, uncertainty regarding long-term effectiveness, and cost-related concerns. The paper further provides a comprehensive analysis of the ethical issues surrounding EICP from three perspectives: environmental ethics, social ethics, and economic ethics. From an environmental ethics perspective, the potential impacts of EICP on ecosystems and the broader environment, as well as its sustainability, are discussed. In terms of social ethics, the discussion emphasizes the social responsibilities involved in the promotion and application of the technology, along with the rights and interests of stakeholders. From an economic ethics standpoint, the paper conducts a cost-benefit analysis and examines issues of fairness in the application of the technology.